(untitled) (International Journal of Engineering and Computer Science, 2015)
The power generated from solar panels cannot be directly used in many applications. One of the key reasons is that the sun is not stationary as it keeps moving from east to west. The solar panels are able to receive peak sun light only for a short time period of day when the sun is directly facing the solar panels. During rest of the day, they get only partial sun light. For this purpose “SUN TRACKER WITH POSITION DISPLAY” is one of the optimal way that allows the solar panel to track the sun’s position, ensuring maximum power generation. Such systems are based on a solar collector, designed to collect the sun’s energy and to convert it into either electrical power or thermal energy. The literature contains many studies regarding the use of solar collectors to implement such applications as light fixtures, window covering systems.